Re-discovery after more than a century: a redefinition of the Malagasy endemic millipede genus Zehntnerobolus, with a description of a new species (Diplopoda, Spirobolida, Pachybolidae) THOMAS WESENER (Germany) - Wesener, Thomas (Zootaxa, 2011)
A new species of the previously monotypic Malagasy pachybolid genus Zehntnerobolus Wesener, 2009, Z. hoffmani new species, is described. The diagnosis of the genus Zehntnerobolus is updated and new characters of potential phylogenetic importance for the classification of Malagasy Spirobolida are described. The here described specimens are the first known representatives of Zehntnerobolus collected since 1900. The late discovery of another Zehntnerobolus is a clear indication of how little we know about the soil arthropod macrofauna of Madagascar. Particularly the eastern rainforest region and the north of Madagascar are still underexplored. The specimens were collected in the eastern montane rainforest more than 380 km south of the known distribution of the other Zehntnerobolus species. The collection method used, as well as morphological parameters of Zehntnerobolus indicate that its species live in the leaf litter of Malagasy rainforests.